The Dynamic of Demographic Characters on the Reading Seed Program of Pustaka Negeri Sarawak - Rozaimie, Awang (Southeast Asia Early Childhood Journal, 2024)
Potentially serving as the primary national literacy initiative, the Reading Seed Programme (RSP) by PUSTAKA Negeri Sarawak aims to enculturate a reading culture from an early age. For instance, RSP was invented to promote reading culture by having the pregnant mother read to their infant until the child was three years old. The process is vital to helping children learn to read from a young age and eventually empower them to be independent readers for life. Particularly, the objectives of RSP are to promote reading habits by getting parents to read to their children, strengthen a child’s vocabulary, and develop their confidence, especially in reading. Thus, this paper is primarily designed to investigate the demographic differences between RSP participation and the programme’s objectives, i.e., reading habits, parent’s engagement, vocabulary ability, and confidence development. To assess how well the RSP achieved its goal of assisting toddlers in developing their confidence as readers. An online survey yielded 385 completed responses, representing a 92.33% response rate among RSP participants. The key findings indicated that the age of the child, mode of joining the programme, and year received the RSP’s kits are the most important indicators of the usefulness of the programme (RSP and RSP’s kits) and the programme’s objectives attainment, especially in straightening the child's vocabulary and comprehension and developing their confidence, especially in reading and knowledge. Nonetheless, the results of this study highlighted the novelty of the early literacy programme of the RSP in cultivating the reading culture, parent-child engagement in reading, and preparing children to acquire knowledge.